The effects of the spatial distribution of direct anthropogenic aerosols radiative forcing on atmospheric circulation - Chemke, R; Dagan, G (American Meteorological Society, 2018)
The large uncertainty in estimating the global aerosol radiative forcing (ARF) is one of the major challenges the climate community faces for climate projection. While the global-mean ARF may affect global quantities such as surface temperature, its spatial distribution may result in local thermodynamical and, thus, dynamical changes. Future changes in aerosol emissions distribution could further modulate the atmospheric circulation. Here, the effects of the spatial distribution of the direct anthropogenic ARF are studied using an idealized global circulation model, forced by a range of estimated-ARF amplitudes, based on the Copernicus Atmosphere Monitoring Service data. The spatial distribution of the estimated-ARF is globally decomposed, and the effects of the different modes on the circulation are studied. The most dominant spatial distribution feature is the cooling of the Northern Hemisphere in comparison to the Southern Hemisphere. This induces a negative meridional temperature gradient around the equator, which modulates the mean fields in the tropics. The ITCZ weakens and shifts southward, and the Northern (Southern) Hemisphere Hadley cell strengthens (weakens). The localization of the ARF in the Northern Hemisphere midlatitudes shifts the subtropical jet poleward and strengthens both the eddy-driven jet and Ferrel cell, because of the weakening of high-latitude eddy fluxes. Finally, the larger aerosol concentration in Asia compared to North America results in an equatorial superrotating jet. Understanding the effects of the different modes on the general circulation may help elucidate the circulation’s future response to the projected changes in ARF distribution.